1982
DOI: 10.1159/000250124
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects Due to RO 10-9359 (Tigason)

Abstract: In a retrospective study clinical and hepatotoxic side effects caused by Tigason treatment are investigated. The material consists of data on 27 patients with normal liver function tests at the beginning of treatment. The clinical side effects encountered were: dryness of lips and mucous membranes (n = 14), diffuse hair loss (n = 5), epistaxis (n = 1) and conjunctivitis (n = 1). Abnormal liver function tests (glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, lactate dehydrogenase and alkaline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…A few well-doc umented cases of toxic hepatitis due to Tiga son have been reported previously [1], In our case, it is difficult to place the re sponsibility for the severe toxic hepatitis on either drug alone. It is known that Tigason is carried in the blood by albumin [6] as is 50-70% of the absorbed MTX [4], This sug gests that the hepatotoxic effects might be caused by a cumulation of the side effects of MTX alone due to its displacement from its albumin-binding site.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A few well-doc umented cases of toxic hepatitis due to Tiga son have been reported previously [1], In our case, it is difficult to place the re sponsibility for the severe toxic hepatitis on either drug alone. It is known that Tigason is carried in the blood by albumin [6] as is 50-70% of the absorbed MTX [4], This sug gests that the hepatotoxic effects might be caused by a cumulation of the side effects of MTX alone due to its displacement from its albumin-binding site.…”
Section: Discussionmentioning
confidence: 54%
“…But Tigason may cause hepatotoxic side effects. This has been demonstrated by slightly elevated liver func tion tests, and also a few cases of manifest toxic hepatitis have been described [1,2,5].…”
mentioning
confidence: 94%
“…This is in accordance with the findings of Christiansen et al [7] who, in psoriatic patients, found no significant dif ferences with regard to liver enzymes be tween etretinate and betamethasone. Dam age to the liver has, however, been reported after etretinate [8], but the real implications of these observations are still uncertain. Re sults from prospective controlled studies with liver biopsies are awaited with great in terest [9], Until then patients with known liver disease should not be treated with etret inate.…”
Section: Discussionmentioning
confidence: 99%
“…A transient, slight elevation of one or sometimes more liver tests can be observed in patients on etretinate (Tigason, Ro 10-9359) therapy [1,6] and at least in some pa tients appears to be provoked by etretinate itself. Very mild damage of the parenchymal tissue in the liver biopsy of such a patient has been reported [9], A histologically con firmed hepatitis supposedly due to etretinate has been described in only 3 patients so far [ 1,8].…”
mentioning
confidence: 99%
“…Very mild damage of the parenchymal tissue in the liver biopsy of such a patient has been reported [9], A histologically con firmed hepatitis supposedly due to etretinate has been described in only 3 patients so far [ 1,8].…”
mentioning
confidence: 99%